Will pre‐adaptation buffer the impacts of climate change on novel species interactions?. Issue 2 (9th August 2013) - Herstoff, Emily; Urban, Mark C.
<x xml:space="preserve">Abstract</x> Species are expected to alter their ranges as climates change. Climate‐induced range expansions of predators could threaten evolutionarily naïve prey populations, leading to high mortality at the invasion front. If prey can apply existing defenses against local predators to novel predation threats induced by climate change, mortality threats will be less than expected. Here, we examine if spotted salamander larvae Ambystoma maculatum from populations that coexist with native red‐spotted newts Notophthalmus viridescens survive better when exposed to a novel predator, the marbled salamander Ambystoma opacum. We show that regional mean winter temperatures warmed 2.0°C over 116 yr in the region, and that A. opacum survival increases in ponds with higher winter temperatures. Hence as winters continue to warm, this apex predator will likely colonize ponds north of their current range limit. Next, we performed common garden experiments to determine if local adaptations to native N. viridescens and exposure to A. opacum or N. viridescens kairomones (predator chemical cues) altered A. maculatum survival in predation trials. We did not find evidence for local adaptation to N. viridescens. However, A. maculatum from high‐N. viridescens ponds that were reared with A. opacum kairomones suffered significantly higher mortality from the native predator N. viridescens. This outcome suggests an unanticipated interaction between local adaptation and plastic responses to novel kairomones from a potentially range‐expanding predator. Current projections of biodiversity losses from climate change generally ignore the potential for eco‐evolutionary interactions between native and range‐expanding species and thus could be inaccurate.